Endothelial Transcytosis of Lipoproteins in Atherosclerosis - Zhang, Xinbo; Sessa, William C.; Fernández-Hernando, Carlos (Frontiers in Cardiovascular Medicine, 2018)
Seminal studies from Nikolai Anichckov identified the accumulation of cholesterol in the arteries as the initial event that lead to the formation of atherosclerotic plaques. Further studies by Gofman and colleagues demonstrated that high levels of circulating low-density lipoprotein cholesterol (LDL-C) was responsible for the accelerated atherosclerosis observed in humans. These findings were confirmed by numerous epidemiological studies which identified elevated LDL-C levels as a major risk factor for cardiovascular disease. LDL infiltrates in the arterial wall and interacts with the proteoglycan matrix promoting the retention and modification of LDL to a toxic form, which results in endothelial cell (EC) activation and vascular inflammation. Despite the relevance of LDL transport across the endothelium during atherogenesis, the molecular mechanism that control this process is still not fully understood. A number of studies have recently demonstrated that low density lipoprotein (LDL) transcytosis across the endothelium is dependent on the function of caveolae, scavenger receptor B1 (SR-B1), activin receptor-like kinase 1 (ALK1) and LDL receptor (LDLR), whereas high-density lipoproteins (HDL) and its major protein component apolipoprotein AI transcytose ECs through SR-B1, ATP-Binding cassette transporter A1 (ABCA1) and ABCG1. In this review article, we briefly summarize the function of the EC barrier in regulating lipoprotein transport, and its relevance during the progression of atherosclerosis. A better understanding of the mechanisms that mediate lipoprotein transcytosis across ECs will help to develop therapies targeting the early events of atherosclerosis and thus exert potential benefits for treating atherosclerotic vascular disease.